Media Reality of Modern Education: Historiography of the Problem of Media Literacy and Media Competence - Svitlana Loboda (Journal of Vasyl Stefanyk Precarpathian National University)
The modern educational paradigm exists in media reality. Accordingly, the challenges and trends of the modern educational space are formed around the problem of media literacy and media competence. The aim of the study is to analyze the best educational practices of the United States, Canada and the United Kingdom in the sphere of media literacy and media competence in order to identify the innovative potential of modern reforms, understand and realize modern processes in education, and design its future.